Characteristics and outcomes of older patients hospitalised for COVID-19 in the first and second wave of the pandemic in The Netherlands: the COVID-OLD study. (1st March 2022) - Smits, Rosalinde A L; Trompet, Stella; van der Linden, Carolien M J; van der Bol, Jessica M; Jansen, Steffy W M; Polinder-Bos, Harmke A; Willems, Hanna C; Barten, Dennis G; Blomaard, Laura C; de Boer, Mark G J; van Deudekom, Floor J A; Ellerbroek, Jacobien L J; et al.
Abstract: Background: as the coronavirus disease of 2019 (COVID-19) pandemic progressed diagnostics and treatment changed. Objective: to investigate differences in characteristics, disease presentation and outcomes of older hospitalised COVID-19 patients between the first and second pandemic wave in The Netherlands. Methods: this was a multicentre retrospective cohort study in 16 hospitals in The Netherlands including patients aged ≥ 70 years, hospitalised for COVID-19 in Spring 2020 (first wave) and Autumn 2020 (second wave). Data included Charlson comorbidity index (CCI), disease severity and Clinical Frailty Scale (CFS). Main outcome was in-hospital mortality. Results: a total of 1, 376 patients in the first wave (median age 78 years, 60% male) and 946 patients in the second wave (median age 79 years, 61% male) were included. There was no relevant difference in presence of comorbidity (median CCI 2) or frailty (median CFS 4). Patients in the second wave were admitted earlier in the disease course (median 6 versus 7 symptomatic days; P < 0.001). In-hospital mortality was lower in the second wave (38.1% first wave versus 27.0% second wave; P < 0.001). Mortality risk was 40% lower in the second wave compared with the first wave (95% confidence interval: 28–51%) after adjustment for differences in patient characteristics, comorbidity, symptomatic days until admission, disease severity and frailty. Conclusions: compared with older patients hospitalised in the first COVID-19 wave, patients in the second wave had lower in-hospital mortality, independent of risk factors for mortality. The better prognosis likely reflects earlier diagnosis, the effect of improvement in treatment and is relevant for future guidelines and treatment decisions.